2015
DOI: 10.1002/hed.24218
|View full text |Cite
|
Sign up to set email alerts
|

External beam radiotherapy in differentiated thyroid carcinoma: A systematic review

Abstract: External beam radiotherapy (EBRT) is not a first line treatment in differentiated thyroid carcinoma (DTC), but is recommended as an adjuvant treatment in certain cases. The evidence for EBRT in DTC is limited. A comprehensive literature search was performed. Data on patient demographics, disease stage, treatment characteristics, and outcomes were collected from included articles after quality appraisal. Sixteen articles met the inclusion criteria, with a pooled population of 5114. Only 1 study was prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 25 publications
0
26
1
Order By: Relevance
“…A recently published systematic review by Fussey et al 32 confirms the improvement in loco-regional control with EBRT in the older patient population with high-risk features.…”
Section: Ebrt Therapymentioning
confidence: 85%
“…A recently published systematic review by Fussey et al 32 confirms the improvement in loco-regional control with EBRT in the older patient population with high-risk features.…”
Section: Ebrt Therapymentioning
confidence: 85%
“… 21 Some studies revealed that EBRT has been traditionally used to treat incompletely resected tumors, unresectable diseases, and aggressive variants, and to reduce the risk of locoregional recurrence. 27 , 28 Other retrospective reviews failed to show any differences in loco-regional control and survival between patients who had received EBRT and those who had not. 29 Interestingly, EBRT and radioactive implants were risk factors for 10-year DSS in CCV patients according to our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the sparse reports regarding EBRT in locally advanced DTC, it has been suggested that EBRT is indicated in patients with gross postoperative disease, positive resection margins, T4 disease or N1b stage in papillary thyroid carcinoma . In a recent systematic review, an improvement in locoregional control is demonstrated when EBRT is used in patients at high risk for LRR and over the age of 45, even though further long‐term multicenter prospective research is warranted . In contrast, retrospective cohort study using the data from the National Cancer Data Base (NCDB) revealed that EBRT was associated with poorer survival outcomes, particularly with papillary thyroid carcinoma, whereas RAI was associated with improved 5‐ and 10‐year survival for advanced stage papillary thyroid carcinoma and follicular thyroid carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…| 881 even though further long-term multicenter prospective research is warranted. 19 In contrast, retrospective cohort study using the data from the National Cancer Data Base (NCDB) revealed that EBRT was associated with poorer survival outcomes, particularly with papillary thyroid carcinoma, whereas RAI was associated with improved 5-and 10-year survival for advanced stage papillary thyroid carcinoma and follicular thyroid carcinoma. 20 Up to date, it is well accepted that adjuvant, postoperative EBRT is recommended for patients with DTC at high risk for LRR, however, its clinical efficacy is still needed to be validated in prospective trials.…”
Section: Figurementioning
confidence: 99%